Pengaruh Layanan Pembelajaran dalam Bimbingan dan Konseling terhadap Prestasi Akademik Peserta Didik SMP - Ayuning Nur Hasanah; Dewinta Warsih; Hanifah Muslimah; Ilman Azmi; Muhammad Minan Chusni (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2024)
This study aims to evaluate the effect of guidance and counseling services on student academic achievement at SMPN 54 Bandung. The focus of the research is on aspects of service quality, student satisfaction, learning effectiveness, increased motivation, and the impact of services on academic achievement. The type of research method used is a quantitative method with a survey approach. This method was chosen to obtain data that can be measured and analyzed statistically. This study involved subjects consisting of 30 students 8th grade junior high school, who were randomly selected with a balanced composition between male students (15 students) and female students (15 students). The random sample selection aims to get a good representation of the population. The results showed that learning services in guidance and counseling have a strong influence on the academic achievement of junior high school students. Based on the analysis of five aspects measured through questionnaires, it can be seen that the aspects of Experience, Motivation, Effectiveness, Quality, and Satisfaction all show “Strong” criteria with the average percentage of each aspect in the range of 76% to 79%.This study shows that learning services in guidance and counseling have a significant and positive influence on the academic achievement of junior high school students. These results indicate that guidance and counseling services in schools are not only well received by students but also markedly contribute to improving their academic achievement.